ANALISIS PEMASARAN KERIPIK MELINJO PADA INDUSTRI CITRA LESTARI PRODUCTION DI KOTA PALU - Muslaeni, Yuniarsih (AGROTEKBIS, 2019)
The marketing analysis of “Keripik Melinjo” on the Citra Lestari Production Industry in Palu City. The purpose of this research is to know the form of marketing channels, the magnitude of margin marketing and the level of “Keripik Melinjo’s” marketing efficiency in the Citra Lestari Production Industry in Palu City. Tools of the analysis are descriptive analysts and margin analysis marketing. The magnitude of the margin marketing on the first line from manufacturer to retailers is Rp 2.400, meanwhile on the second line it has no margin marketing, because there is no intermediary trader involved in the marketing, the consumer come directly to the manufacturer to buy “Keripik Melinjo”. The magnitude of the price received by Citra Lestari Production Industry manufacturer on the first channel is 83,33%, while the magnitude of the price on the second channel is 100%. The level of efficiency achieved by manufacturer on the first line is 34,22%, while on the second line is 32,63%.